Country Partnership Framework for the Federal Republic of Somalia for the Period FY19-FY22 - World Bank Group (World Bank, Washington, DC, 2018)
This Country partnership framework (CPF) (FY19-FY22) will help Somalia consolidate its transition by investing in services and economic opportunities while continuing to address the structural drivers of fragility. Based on the Systematic Country Diagnostic (SCD) and wide-ranging consultations, the Bank Group will support priorities in two Focus Areas: (i) building institutions to deliver services, and (ii) restoring economic resilience and opportunities. Building on good country performance, the World Bank Group (WBG’s) engagement will expand under this CPF, with new exceptional financing from IDA’s pre- arrears clearance grants. In Focus Area 1, the WBG will strengthen ongoing governance programs with a new focus on fiscal space and improving access to and quality of key social services and resilience. Under Focus Area 2 the WBG aims to increase economic resilience as a basis for long-run poverty reduction and inclusive growth.